2021
DOI: 10.1093/gastro/goab035
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut microbiota in functional constipation

Abstract: Functional constipation (FC) is common, yet the etiology is not clear. Accumulating evidence suggests an association between FC and abnormal gut microbiota. The relationship between the gut microbiota and the gut transit is likely bidirectional. This review summarizes the current evidence regarding the impact of gut microbiota on the pathogenesis of FC. By modulating the colonic motility, secretion, and absorption, gut microbiota may contribute to the development of FC through microbial metabolic activities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 104 publications
2
59
0
1
Order By: Relevance
“…For example, when antibiotics deplete intestinal bacteria who are responsible for converting primary bile acids into secondary bile acids, such as deoxycholate, lithocholate, ursodeoxycholate, hyodeoxycholate, and ω-muricholate, the resistance to Clostridium difficile decreases [ 23 ], resulting in pseudomembranous colitis and persistent diarrhoea that claim lives of tens of thousands of people in the US [ 24 , 25 ]. Likewise, it is now well-accepted that a dysbiosis of gut microbiome can affect not only inflammatory bowel disease (IBD), constipation, indigestion, and obesity but also the occurrence and prognosis of hypertension, diabetes, cancer, and cardiovascular diseases (CVD) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Hyperpermeable Intestine—leaky Gutmentioning
confidence: 99%
“…For example, when antibiotics deplete intestinal bacteria who are responsible for converting primary bile acids into secondary bile acids, such as deoxycholate, lithocholate, ursodeoxycholate, hyodeoxycholate, and ω-muricholate, the resistance to Clostridium difficile decreases [ 23 ], resulting in pseudomembranous colitis and persistent diarrhoea that claim lives of tens of thousands of people in the US [ 24 , 25 ]. Likewise, it is now well-accepted that a dysbiosis of gut microbiome can affect not only inflammatory bowel disease (IBD), constipation, indigestion, and obesity but also the occurrence and prognosis of hypertension, diabetes, cancer, and cardiovascular diseases (CVD) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Hyperpermeable Intestine—leaky Gutmentioning
confidence: 99%
“…Severe constipation can cause gastrointestinal nerve dysfunction and even induce cancer and cardiovascular and cerebrovascular diseases ( Nishitani-Yokoyama et al., 2021 ; Huang et al., 2022 ). A large number of studies have shown that probiotics can shorten gastric emptying time and intestinal transit time, enhance the peristaltic transmission function of the gastrointestinal tract, and help relieve constipation ( Zhang et al., 2021 ). We selected Bifidobacteria treated with different embedding methods to determine whether the embedding method affected the strains’ effectiveness in relieving constipation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when antibiotics deplete intestinal bacteria who are responsible for converting primary bile acids into secondary bile acids, such as deoxycholate, lithocholate, ursodeoxycholate, hyodeoxycholate, and ω-muricholate, the resistance to Clostridium difficile decreases [23], resulting in pseudomembranous colitis and persistent diarrhea that claim lives of tens of thousands of people in the US [24,25]. Likewise, it is now well-accepted that a dysbiosis of gut microbiome can affect not only inflammatory bowel disease (IBD), constipation, indigestion, and obesity, but also the occurrence and prognosis of hypertension, diabetes, cancer, and cardiovascular diseases (CVD) [26][27][28][29][30][31][32][33].…”
Section: Hyperpermeable Intestine -A Leaky Gutmentioning
confidence: 99%